CORRELATION OF FIRST DIGIT DACTYLOGRAPHY WITH RETINAL VASCULAR PATTERNS: AN OBSERVATIONAL STUDY. - Walia, Sween; Bhavna; Maheshwari, Shubhangi (Student’s Journal of Health Research Africa, 2024)
BACKGROUND The retina is the only bodily area where the microvascular bed is visible, making it perfect for studying sequestration non-invasively in vivo and real life. Therefore, the present study was designed to find a correlation between 1st digit patterns with retinal vascular patterns. MATERIALS & METHODS The present study was conducted on 200 subjects. Digital photographs of the fundus of the eyes were taken with a fundus camera. Eyes were divided into superior and inferior quadrants on both the nasal and temporal sides of the eyes, then, the retinal vasculature was studied and analyzed. 1stdigit prints were taken and dermatoglyphic patterns were observed using a magnifying glass. Data obtained by studying retinal vascular patterns were compiled and findings were compared with 1st digit prints. Then, all the data so collected was recorded, tabulated, and analyzed. RESULT 39% of subjects had loop patterns, 36.5% had whorls, and 1.5% had arches on their first digit. Retinal vasculature was more extensive on the temporal side in 87.5% of subjects. Subjects with loops on both thumbs had a higher mean number of branches in the superotemporal quadrant of the left eye (mean = 9.36, SD = 3.12), while those with whorls had more branches in the superotemporal quadrant of the right eye (mean = 9.34, SD = 2.87). These findings indicate a notable correlation between first-digit fingerprint patterns and retinal vascular branching. CONCLUSION This is the first published paper showing an important observation as both biometrics are genetically regulated. However, this correlation whether causal or effective cannot be explained as further research is needed and this data may provide a reference for future research. RECOMMENDATIONS Further research using advanced biometric tools is recommended to explore the causal relationship between fingerprint patterns and retinal vascular branching, potentially enhancing the efficacy of biometric identification methods.